Atypical vascular lesion in the abdominal wall: Differential diagnosis between benign and malignant, Case report. - S*., Carrillo Barraza; E.I., Sanchez Sampedro; L. de M., Morán Luna (Revista de Ciencias Médicas Torreón, 2025)
Among atypical vascular lesions, we can identify hemangiomas and angiosarcomas. The former are described as benign neoplasms more common in childhood and predominantly present in the abdominal wall. Angiosarcomas, on the other hand, are malignant neoplasms with greater aggressiveness, presenting progressively growing lesions, ulceration, and spontaneous bleeding. They are most commonly located on the scalp and face, with a high rate of recurrence and metastasis. We present the clinical case of a 60-year-old male patient with a 10-year history of ulcerative lesion on his left flank, which had been developing slowly and was bleeding spontaneously. A biopsy was taken, and a surgical procedure was performed with wide resection and local flap rotation. The biopsy result revealed a hemangioma, so the variable presentation of hemangiomas and their simulation for malignant lesions can be discussed.